An Analysis of The Conflict between the Right to Information Act 2005 and Official Secrets Act 1923 in India - Kushwaha, Ayushi; Chengappa, MP (Christ University Law Journal, 2025)
The 2019 Rafale deal case facilitated the reemergence of an old debate between official secrecy and transparency, which now invites more scholarship with the introduction of the Right to Information Act (RTI Act 2005). The legislation intends to maximise the dissemination of information kept by public authorities, with only limited exceptions where it can be withheld. With such a profound impact on how information should be handled by public authorities, the governmental obsession with the colonial Official Secrets Act 1923 (OSA 1923) attracts scrutiny. Unlike the RTI Act 2005, which streamlines the framework on what and how information with the government can be made available, the OSA 1923, which is concerned with the regulation of official secrets in the country, is silent on the limits of withholding. Under the colonial framework, the government is empowered to classify without exception, criminalise any wrongful disclosure (sensitive or not), and minimise transparency otherwise aimed at under the RTI Act 2005. It is time that the OSA 1923 is harmonised with the RTI Act 2005, with its glaring inconsistencies. In this paper, the author argues that the OSA 1923 has become obsolete and should be harmonised with the RTI Act 2005 to prevent the dilution of the latter.